PSYCHOLOGICAL WELL-BEING IN DIFFERENT TYPES OF REPRODUCTIVE NORMATIVITY - Zmievskaya, Anastasia Aleksandrovna; Kurysheva, Olga Vasilievna (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2017)
The article investigates the reproductive normativity in the context of its relationship to person’s psychological well-being. The theoretical analysis allowed to formulate the definition of reproductive normativity (RN) and its structural components. It’s considered the problem of relation between objective and subjective components of RN as the determinant of psychological well-being. It’s presented and justified one of the possible typologies of RN, reflecting the most common variants of modern Russians’ reproductive behavior: 1) high RN («The total normativity»); 2) medium-high RN («Family with deviant past»); 3) medium-low RN («Single parenthood»); 4) low RN («No family and children»). The presence of different relations between objective and subjective components of RN in described types is empirically detected. The highest consistency of RN components is observed in groups with high and low RN, the lowest consistency is manifested among single parents. The mismatch between RN components is associated with lower psychological well-being. Single parents are at risk: they demonstrate the most negative evaluations of their life, self-awareness and self-attitude. Average- auspicious and almost identical indicators of psychological well-being were found among respondents with deviant past (medium-high RN) and respondents with no family and children (low RN): psychological benefits of having family and children are eliminated by abnormal parenthood experience and by the mismatch between desired and actual implementation of family life. Thereby the «blocked» parent role is connected with the same level of psychological well-being as the improperly played parent role. The highest level of psychological well-being is expectedly found among respondents with high RN («The total normativity»).